Determination of moisture content and grain angle of Malaysian wood species using the microwave transmission technique in the frequency range of 8 to 12 GHz / Sulaiman Abdul Malik - Abdul Malik, Sulaiman (2007)
Microwave Non-Destructive Testing (MNDT) are fast, contact-less, accurate and continuous techniques for the evaluation of physical properties of wood such as moisture content, slope-of-grain and density using microwave. The Free Space Microwave Measurement (FSMM) system has been developed for this purpose. The system consists of a pair of spot-focusing horn lens antennas mounted on a table connected to the two ports of Wiltron37269B Vector Network Analyzer (VNA) using precision coaxial cables, rectangular-to-circular and coaxial-to-rectangular waveguide adapters. A calibration and optimization procedure was performed to the FSMM system before using it. Microwave at the frequency range of 8 to 12GHz was propagated through the wood specimen placed between two antennas and the reflection coefficient (Sn) and transmission coefficient (S21) was measured. In this research, the S21 coefficient has been used to measure the permittivity of wood. The permittivity of wood comprises of two components, the dielectric constant {s') and loss factor {e"). Since wood is an anisotropic material, therefore s' ande" of the wood varies when measured at different angles to the wood grain. A data base of f'and^"of twenty-five Malaysian wood species, measured at (/(parallel), 30°, 60° and 90°(perpendicular) to wood grain has been developed for future use. All measurements were made in the laboratory at temperatures of between 25±2°C was undertaken. A study on measuring the moisture content and wood grain angle using the FSMM system of three wood species specimen of Kempas {Koompassia malaccensis),Yellow Meranti {Shorea spp) and Petai (Parkia spp) was undertaken. The measurement of wood grain angle only was carried on Medang specie {Specie of Lauraceae) was carried out. The wood specimen <?' and s" were measured at several moisture content levels from saturated to oven-dry states at an angle from 0° to 90° to the wood grain. The measured s' was then used to calculate the wood's moisture content based on several new models adopted from the Mixture Theory and Theory of Grain Angle measurement. The study shows that the measured f'and moisture content is dependent on wood grain angle and density and microwave's frequency.